Aqua(trifluoromethanesulfonato)bis(1,3,7-trimethylpurine-2,6-dione)silve r(I) - Arman, H.D.; Miller, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, [Ag(CF(3)SO(3))(C(8)H(10)N(4)O(2))(2)(H(2)O)], the Ag I atom is coordinated by two caffeine N atoms and, at longer distances, two O atoms of a coordinated water molecule and the trifluoromethanesulfonate anion, resulting in an AgN(2)O(2) seesaw geometry. The caffeine molecules are roughly coplanar [dihedral angle = 5.81 (5)degrees]. In the crystal, molecules self-assemble into a linear supramolecular chain along the c axis via O-H center dot center dot center dot O hydrogen bonds involving the coordinated water moledcule and carbonyl O atoms. The packing is consolidated by weak C-H center dot center dot center dot O interactions.